Interstitial 22q13 deletions not involving SHANK3 gene: A new contiguous gene syndrome. Issue 7 (3rd April 2014) - Disciglio, Vittoria; Rizzo, Caterina Lo; Mencarelli, Maria Antonietta; Mucciolo, Mafalda; Marozza, Annabella; Di Marco, Chiara; Massarelli, Antonio; Canocchi, Valentina; Baldassarri, Margherita; Ndoni, Enea; Frullanti, Elisa; Amabile, Sonia; et al.
<x xml:space="preserve">Abstract</x> Phelan–McDermid syndrome (22q13.3 deletion syndrome) is a contiguous gene disorder resulting from the deletion of the distal long arm of chromosome 22. SHANK3, a gene within the minimal critical region, is a candidate gene for the major neurological features of this syndrome. We report clinical and molecular data from a study of nine patients with overlapping interstitial deletions in 22q13 not involving SHANK3. All of these deletions overlap with the largest, but not with the smallest deletion associated with Phelan–McDermid syndrome. The deletion sizes and breakpoints varied considerably among our patients, with the largest deletion spanning 6.9 Mb and the smallest deletion spanning 2.7 Mb. Eight out of nine patients had a de novo deletion, while in one patient the origin of deletion was unknown. These patients shared clinical features common to Phelan–McDermid syndrome: developmental delay (11/12), speech delay (11/12), hypotonia (9/12), and feeding difficulties (7/12). Moreover, the majority of patients (8/12) exhibited macrocephaly. In the minimal deleted region, we identified two candidate genes, SULT4A1 and PARVB (associated with the PTEN pathway), which could be associated in our cohort with neurological features and macrocephaly/hypotonia, respectively. This study suggests that the haploinsufficiency of genes in the 22q13 region beside SHANK3 contributes to cognitive and speech development, and that these genes are involved in the phenotype associated with the larger Phelan–McDermid syndrome 22q13 deletions. Moreover, because the deletions in our patients do not involve the SHANK3 gene, we posit the existence of a new contiguous gene syndrome proximal to the smallest terminal deletions in the 22q13 region. © 2014 Wiley Periodicals, Inc.